Advancements in the treatment of osteochondral lesions of the talus - Lianjie Cheng; Xuena Wang (Journal of Orthopaedic Surgery and Research)
Abstract Osteochondral lesions of the talus (OLT) are common ankle joint pathologies, often caused by traumatic or non-traumatic factors. Due to the anatomical characteristics and limited blood supply of the talus, the spontaneous healing capacity of OLT is poor, posing challenges for clinical treatment. Traditional treatments include conservative therapy and surgical interventions, but their efficacy is limited. In recent years, significant advancements in OLT treatment have been achieved with developments in biomaterials science, cell biology, and tissue engineering. This article summarizes the latest research progress in various treatment methods, including conservative treatment, bone marrow stimulation, chondrocyte transplantation, and osteochondral grafting, and evaluates the role of biological augmentation agents such as platelet-rich plasma (PRP) and concentrated bone marrow aspirate (CBMA) in promoting cartilage repair. Additionally, the application of biological scaffold technology offers new prospects for cartilage regeneration. Although emerging therapies show potential in clinical practice, further research is needed to evaluate their long-term efficacy, indications, and safety. This article aims to provide valuable references for clinicians, researchers, and policymakers, promoting the development and refinement of OLT treatment strategies.